A New Approach to Optimize Over Current Relay Coordination - Ismu Wijayanto; Sasongko Pramono Hadi (Prosiding 2nd Seminar Nasional IPTEK Terapan (SENIT) 2017, 2017)
A power system can not be separated from interference. Interruptions in  power system may interfere service continuity  and potentially damage equipment due to fault current flow on the line. Therefore, it is needed a protection system that can isolate  disturbed area and can avoid equipment damage. Many relays installed in power protection systems,  and overcurrent relay is an important protective device and widely installed in the power system. This relay is useful to protect equipment from current spikes during interruption or flashover occurs. An electric power protection system can work optimally if there is coordination of installed overcurrent current relay. This research is expected to be useful for optimizing the overcurrent relay coordination protection.